Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Dengan Reputasi Perusahaan Sebagai Variabel Mediasi - Ni Ketut Maya Diani; Ni Luh Putu Ratna Wahyu Lestari; Putu Gede Wisnu Permana Kawisana (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
There are several phenomena in this research, namely, the company does not process waste from production raw materials, violations of consumer rights, negligence towards employee safety and health and fraud in financial performance reports by manipulating revenue recognition. This research aims to empirically test the influence of Corporate Social Responsibility on Financial Performance, the Influence of Corporate Social Responsibility on Corporate Reputation, the Influence of Corporate Reputation on Financial Performance and the Influence of Corporate Reputation as a mediating variable between Corporate Social Responsibility and Financial Performance. The sample determined was determined based on the purposive sampling method, with a total sample of 21 issuers so that the total observations in this study were 63 observations. The data used in this research is secondary data. The data analysis technique for testing hypotheses is Partial Least Square. The research results prove that (1) Corporate Social Responsibility has a significant positive effect on Financial Performance, (2) Corporate Social Responsibility has a significant positive effect on Corporate Reputation, (3) Corporate Reputation has a significant positive effect on Financial Performance (4) Corporate Reputation can mediate the influence of Corporate Social Responsibility for Financial Performance.